(untitled) (Community Based Medical Journal, 2014)
Bardet Biedl syndrome is a rare autosomal recessive condition with a wide spectrum of clinical features. The accepted major criteria for diagnosis include obesity, polydactyly, male hypogonadism, mental retardation, retinal dystrophy, adrenal dysfunction. We have presented a 14 year old male patient exhibiting characteristic features of Bardet Biedl syndrome (BBS), admitted into Community Based Medical College Hospital. CBMJ 2014 January: Vol. 03 No. 01 P: 56-59